Redefining global strategy : crossing borders in a world where differences still matter - Ghemawat, Pankaj (Harvard Business Review Press, 2018)
Why do so many global strategies fail--despite companies' powerful brands and other border-crossing advantages? Seduced by market size, the illusion of a borderless, "flat" world, and the allure of similarities, firms launch one-size-fits-all strategies. But cross-border differences are larger than we often assume, explains Pankaj Ghemawat in Redefining Global Strategy, with a New Introduction. Most economic activity--including direct investment, tourism, and communication--happens locally, not internationally. In this "semi-globalized" world, one-size-fits-all strategies don't stand a chance. Companies must instead reckon with cross-border differences. Ghemawat shows you how--by providing tools for: assessing the cultural, administrative, geographic, and economic differences between countries at the industry level and deciding which ones merit attention; tracking the implications of particular border-crossing moves for your company's ability to create value; and creating superior performance with strategies optimized for adaptation (adjusting to differences), aggregation (overcoming differences), and arbitrage (exploiting differences), and for compound objectives. In-depth examples reveal how companies such as Cemex, Toyota, Procter & Gamble, Tata Consultancy Services, IBM, and GE Healthcare have adroitly managed cross-border differences--as well as how other well-known companies have failed at this challenge. Crucial for any business competing across borders, this book will transform the way you approach global strategy.--